Is the tumor cell side of the immunological synapse a polarized secretory domain? - Biolato, Andrea Michela; Filali, Liza; Pereira Fernandes, Diogo; Moreau, Flora; Mgrditchian, Takouhie; Hoffmann, Céline; Thomas, Clément (Frontiers in Immunology, 2024)
The formation of a lytic immunological synapse (IS) is crucial for cytotoxic lymphocytes to accurately target and effectively eliminate malignant cells. While significant attention has been focused on the lymphocyte side of the IS, particularly its role as a secretory domain for lytic granules, the cancer cell side of the IS has remained relatively underexplored. Recent findings have revealed that cancer cells can rapidly polarize their actin cytoskeleton toward the IS upon interaction with natural killer (NK) cells, thereby evading NK cell-mediated cytotoxicity. In this Brief Research Report, we present preliminary findings suggesting that actin cytoskeleton remodeling at the cancer cell side of the IS is associated with the targeted secretion of small extracellular vesicles towards the interacting NK cell. We observed that multivesicular bodies (MVBs) preferentially accumulate in the synaptic region in cancer cells exhibiting synaptic accumulation of F-actin, compared to those lacking actin cytoskeleton remodeling. Extracellular immunofluorescence staining revealed increased surface exposure of CD63 at the cancer cell side of the IS, suggestive of the fusion of MVBs with the plasma membrane. This hypothesis was supported by a pH-sensitive probe demonstrating dynamic trafficking of CD63 to the extracellular region of the IS. Collectively, our data support the notion that cancer cells can engage in targeted secretion of extracellular vesicles in response to NK cell attack, underscoring the need for further research into the potential role of this process in facilitating cancer cell immune evasion.